DEVELOPMENT OF SPECIAL PROTECTIVE CLOTHING AGAINST PESTICIDES USED IN AGRICULTURE - Pulatova Sabokhat Usmanovna; Turayeva Nafisa Abdulloevna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article explores the crucial development of specialized protective clothing designed to mitigate the risks associated with pesticide exposure in agriculture. With a focus on fabric technology and innovative design, the study investigates the effectiveness of these garments in safeguarding the health and well- being of agricultural workers. The research integrates a comprehensive literature analysis, methodological approach, results, and a discussion to provide valuable insights into the advancements in protective clothing against pesticides. The article concludes with practical implications and suggestions for future research and development in this critical field.